2011
DOI: 10.19030/jber.v2i3.2861
|View full text |Cite
|
Sign up to set email alerts
|

Users Attitudes Toward Movie-Related Websites And E-Satisfaction

Abstract: Numerous websites provide information, sell products, and offer services. However, not many websites have focused on usability issues, such as ease of use, usefulness, and customer satisfaction. Therefore, in this paper, the authors first consider what factors affect ease of use and usefulness and then how ease of use and usefulness affect attitudes toward websites and customer satisfaction. This study classified four different user groups based on their degree of involvement to measure different levels of per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Alba et al (1997) mentioned that brand names could help consumers make purchase decisions in the computer-mediated environment as those enable highly reliable inferences about consumption benefits after one purchase and use. Cho and Ha (2004) found that brand name importantly affects consumer choice behavior in the electronic marketplace. This study hypothesizes that brand familiarity affects consumers' perceived usefulness and ease of use with both catalogue and e-businesses.…”
Section: Volume 23 Numbermentioning
confidence: 99%
“…Alba et al (1997) mentioned that brand names could help consumers make purchase decisions in the computer-mediated environment as those enable highly reliable inferences about consumption benefits after one purchase and use. Cho and Ha (2004) found that brand name importantly affects consumer choice behavior in the electronic marketplace. This study hypothesizes that brand familiarity affects consumers' perceived usefulness and ease of use with both catalogue and e-businesses.…”
Section: Volume 23 Numbermentioning
confidence: 99%
“…This theory was developed in the context of traditional media, such as TV, magazines, or radio (McGuire, 1974), but has been extended to the online environment (Luo, 2002). These studies of users' attitudes, social behavior, usability aspects, customer satisfaction and cognitive requirements are valuable for designers when they design websites because they provide insight into how online users become customers, especially loyal customers (Cho & Ha, 2011).…”
Section: Multidisciplinary Interface Designmentioning
confidence: 99%
“…A more important factor than information availability that affects consumer's decisionmaking on the Web is how the dot-com business provides a higher quality of information. Cho and Ha (2003) posit that the quality of information content provided by websites often reduces users' search efforts and agitates behavioral intention to use. This study hypothesizes that online consumers' willingness to purchase increases as their perceived information quality increases.…”
Section: Information Quality Factormentioning
confidence: 99%